Lauttasaaren kartanon väkeä - Mitterhusen, Karl
sisällön kuvaus: Lauttasaaren kartanon väkeä. (= Otavantie 10).
Keywords: saaret; kartanot; pihat; kesä; naiset; miehet; työntekijät; lapset; naisten puvut; lastenvatteet; Suomi, Uusimaa, Helsinki, Lauttasaari Helsinki, Otavantie 10